IMPLEMENTASI E-COMMERCE MENGGUNAKAN LOW CODE PROGRAMMING PADA SAM’S FOODIE BERBASIS RESPONSIVE WEB - Abigail, Michelle Florence; Budi, Akhmad (Jurnal Informatika dan Bisnis, 2023)
Technology continues to develop from time to time. With increasingly sophisticated technology, various information can be obtained easily. One of the visible developments is there’s responsive web that automatically will adjust itself with the device used. The use of the website is not only for getting and uploading information but also used in the business world, which known as E-Commerce. There are many programming languages that can be used in making a website and many developers tend to apply a high code programming in their making. Even though there are new ways to create websites that are easier and faster by implementing low code programming. The design of the website that is made includes the system design described in the UML Diagram. The resulting website is a website in the form of simple E-Commerce that can be opened not only via a computer but also from a mobile device. The aim of this research is to be able to make an E-Commerce website by using the implementation of low code programming so that business needs both in terms of owners and users can be fulfilled. Keywords: Website, E-Commerce, Low Code Programming, Responsive Web